(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The experiment entitled “Performance of organic manures and inorganic fertilizers and their combinations on growth, yield and quality of radish (Raphanussativus L.)” was conducted during the Kharif season of the year 2020 at the Instructional Farm of the Department of Horticulture, AKS University, Satna (M.P.). The experiment was laid out in a Randomized Block Design comprising of 12 treatments each replicated three times. T1- Control (100% RDF), T2- 100% N through FYM, T3100% N through Vermicompost, T4- 100% N through Poultry manure, T5-75 % NPK + 25% N through FYM, T6-75 % NPK + 25% N through Vermicompost, T7-75 % NPK + 25% N through Poultry manure, T8-50 % NPK + 50% N through FYM, T9-50 % NPK + 50% N through Vermicompost, T10-50% NPK + 50% N through Poultry manure, T11- Cow Dung 100%, T12- 75% NPK + Cow Dung 25%. The results revealed that the treatment T1- 100% RDF (120: 80: 50 N, P2O5 and K2O kg/ ha), has emerged as the most effective treatment. Specifically, this treatment has shown significant positive impacts on both the growth and yield of radish crops, particularly when cultivated in the specific conditions of Satna.